Study on the Construction of Safety Management System of Chinese Electric Power Enterprises Based on Systematic Thinking. Issue 1 (March 2021) - Chenggong, Guo; Feng, Jiang; Ying, Li; Yun, Luo
Abstract: In order to clarify the construction process and content of Safety Management System (SMS) and deepen the systematic construction of safety management of power enterprises in China, the paper analyses the current problems of SMS construction of domestic electric power enterprises. A construction method of SMS for China's electric enterprises is proposed based on systematic thinking and system modelling method. Taking State Grid Corporation of China (SGCC) as an example, the construction model of SMS is designed based on the Hall three dimensions structure model. According to China's national regulations and power industry safety management requirements, as well as practical experience of SGCC, ten core elements of the system were screened. The SMS operation cycle of Leadership-Responsibility-Plan-Do-Check-Act (LRPDCA) was designed based on the concept of Plan-Do-Check-Act (PDCA) and the characteristics of China's power safety management. The results have some guidance significance to continually promote safety management capacity of electric power enterprise in the new era.